STRENGTH AND JUMPING ASYMMETRIES IN GYMNAST AND THEIR NON-GYMNAST PEERS - Urška Čeklić; Nejc Šarabon (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
While many studies investigated inter-limb asymmetries (ILAs) in different athletes, little is known about ILAs in the population of gymnasts. The first aim of our study was to compare differences between gymnasts and their non-gymnast peers in isometric knee maximal and rapid strength parameters (peak torque - PT and rate of torque development - RTD) and countermovement jump (CMJ) parameters (height, maximal force), as well as in ILAs in all outcome measures. The second aim of the study was to assess the relationship between ILA of maximal force and the ILAs of the isometric knee strength parameters. 15 gymnasts (aged 11.19 ± 1.89 years) and 15 non-gymnasts (aged 10.92 ± 1.96 years) performed unilateral isometric maximal voluntary contractions of the knee flexors and extensors on a dynamometer and CMJ on a force plate. ILAs were calculated and compared between groups across all outcome measures. We found that gymnasts reached statistically significant better results than non-gymnasts in most isometric knee strength parameters and CMJ height, but not on RTD of left knee flexion and maximal force in the CMJ. Meanwhile, we did not find significant differences between groups in ILAs. Linear regression showed no correlations between the ILAs measures separately for the groups. Even though we did not find any differences between the groups in the ILAs, we should be aware of it to prevent injury in young girls.